2020
DOI: 10.1097/phh.0000000000001262
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Barriers to On-site HIV and HCV Testing Services in Methadone Maintenance Treatment Programs in the United States: Findings From a National Multisite Qualitative Study

Abstract: Context: Few substance use disorder (SUD) treatment programs provide on-site human immunodeficiency virus (HIV) and/or hepatitis C virus (HCV) testing, despite evidence that these tests are cost-effective. Objective: To understand how methadone maintenance treatment (MMT) programs that offer on-site HIV/HCV testing have integrated testing services, and the challenges related to offering on-site HIV/HCV testing. Design: We used the 2014 National Drug Abuse Treatment System Survey to identify outpatient SUD trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Surveys are, however, conducted at OTP facilities to record methadone administration. 19 A series of surveys [20][21][22]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys are, however, conducted at OTP facilities to record methadone administration. 19 A series of surveys [20][21][22]…”
Section: Discussionmentioning
confidence: 99%
“…Surveys are, however, conducted at OTP facilities to record methadone administration. 19 A series of surveys 20 , 21 , 22 conducted via National Drug and Alcohol Testing Systems in 2008 to 2017 documented both dosage patterns in methadone use and found that many practitioners dose underrecommended levels, particularly in racially underrepresented populations. However, the National Survey of Substance Abuse Treatment Services and National Drug and Alcohol Testing Systems do not have data on individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, despite the need, feasibility and value of on-site HIV testing in these viable settings, most programs do not offer testing, with less than half of U.S. SUD programs and less than one-third of OTPs offering on-site HIV testing [ 14 ]. Prior research has noted many significant organizational-level and client-level barriers preventing widespread HIV testing uptake in these treatment settings, including lack of reimbursement and insufficient billing systems, constraints surrounding staffing, resources, training and workflow, and concerns about delivering HIV test results and linkage to care [ 14 16 ]. In addition, research has shown greater prioritization and perceived need for hepatitis C virus (HCV) testing compared to HIV testing, given the higher prevalence of HCV compared to HIV within this population [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, despite the need, feasibility and value of on-site HIV testing in these viable settings, most programs do not offer testing, with less than half of U.S. SUD programs and less than one-third of OTPs offering on-site HIV testing (14). Prior research has noted many significant organizational-level and client-level barriers preventing widespread HIV testing uptake in these treatment settings, including lack of reimbursement and insufficient billing systems, constraints surrounding staffing, resources, training and workflow, and concerns about delivering HIV test results and linkage to care (14)(15)(16). In addition, research has shown greater prioritization and perceived need for Hepatitis C virus (HCV) testing compared to HIV testing, given the higher prevalence of HCV compared to HIV within this population (17,18).…”
Section: Introductionmentioning
confidence: 99%